In vitro Evaluation of Finasteride Tablets Produced in Iran with the Tablets Imported from Abroad - ASHNAGAR, A.; GHARIB NASERI, N.; KHODADADZADEH, G.R.; SALIMI, A. (Asian Journal of Chemistry, 2010)
Finasteride, a synthetic 4-azasteroid suppresses DHT by about 70 % in serum and by as much as 85-90 % in the prostate. Finasteride with a 5 mg daily dose has been used for the treatment of Benign Prostatic Hyperplasia (BPH) and with a 1 mg dose for the treatment of male pattern baldness. In this research, the extent of hardness, disintegration time, percentage of active ingredient and dissolution rates of finasteride tablets produced by Mehrdaru and Sohahelal Pharmaceutical Companies of Iran and three corresponding foreign tablets such as (Proscar of England, Fincar of Canada and Fincar of India) and finasteride standard powder, were investigated and comparison between them were made thoroughly. It was found that finasteride tablets produced by Mehrdaru and Sohahelal Pharmaceutical Companies of Iran have the standard limits proposed by the internationally well known Pharmacopoeia and are comparable with the corresponding foreign tablets such as (Proscar of England, Fincar of Canada and Fincar of India) and can satisfy the needs of patients quite well.